THE UNDERSTANDING OF THE DIPLOMACY CONCEPT AND THE HISTORICAL DEVELOPMENT OF DIPLOMATIC TERMINOLOGY (Proceedings of International Educators Conference, 2024)
Diplomacy, as a fundamental aspect of international relations, has changed significantly over the centuries, affecting the way countries interact and negotiate with each other. This article explores the multifaceted nature of diplomacy, its conceptual evolution, and the historical development of key diplomatic terms. Tracing the origins and transformations of diplomatic practice and terminology, this study provides a comprehensive understanding of how diplomacy has shaped global politics and continues to play a crucial role in contemporary international affairs.